PENINGKATAN HASIL BELAJAR GULING DEPAN MELALUI MEDIA PEMBELAJARAN AUDIO VISUAL PADA KELAS VIII SMP NEGERI 5 SEMARANG TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to improve student learning outcomes through audio-visual media in teaching gymnastics at the front of the class bolsters SMP Negeri 5 Semarang. This study used a descriptive quantitative research methods and types of research is a class action consisting of four stages : planning , action , observation , and reflection. Data collection techniques used were tests , observation sheets and questionnaires. In the first cycle of learning outcomes obtained a mean score of 70.2 category ( good ) taken from three aspects, namely psychomotor assessment criteria a mean value ( 71.8 ) , affective a mean value ( 68.5 ) and cognitive the mean value ( 70.4 ) , the results it can be concluded that student learning outcomes are good enough but needs to be improved. While in Cycle II study results obtained mean score of 85.8 category ( good ) taken from three aspects , namely psychomotor assessment criteria with a mean value ( 88.3 ) , affective with a mean value ( 85.0 ) and cognitive with the mean value ( 84.2 ) , of the results can be concluded that student learning outcomes have been good ( Completed All) in keeping with KKM in the set , namely ( 80.00 ). Can be summed scores increased student learning outcomes . Thus the use of audio-visual media in teaching learning gymnastics forward roll can increase motivation , comprehension and learning outcomes eighth grade students of SMP Negeri 5 Semarang .